AN INTERNATIONAL EFFORT TOWARD A DEMOCRATIZATION IN CURRENT AFFIARS INFORMATION (NEWS) PROCESSING: CRITIQUE OF THE NEW WORLD INFORMATION ORDER: UN EFFORT INTERNATIONAL POUR LA DEMOCRATISATION DU TRAITEMENT DE L’INFORMATION (NOUVELLES) SURE LES AFFAIRES PUBLIQUES: UNE CRITIQUE D’UN NOUVEL ORDRE MONDIAL DE L’INFORMATION - Diener, Richard A.V. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2022)
See PDF